Analysis and Risk Study on Landslide Hazard Frequency at Road Corridor of Batu City – Kediri Regency Border - Emil Wahyudianto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Road corridor of Kota Batu – Kediri Regency Boundary is a provincial road that has a vital function for the economic and tourism movement from and to Batu City in East Java Province. This inter-regency road is historically vulnerable to disaster events such as landslide, Kali Konto flash flood, Kelud Mountain lahar, flood inundation, etc. This research was referred to Regulation of Ministry of Public Work No.22/PRT/M/2007 on Guidelines for Spatial Planning of Landslide Vulnerable Areas and helped with Geographic Information System (GIS). Method comparison was also conducted by Meiliana (2011) with the indicators from the same regulation, and by using Landslide Hazard Assessment (LHA) method that is based on historical data. The landslide risk mapping with LHA method that is combined with analysis result from the vulnerability of moving vehicles is suggested to be the reference in mapping the mass-movement disaster risk on Indonesian road corridors. Analysis on frequency of rainfall that triggered landslide concluded that the probability of landslide occurrence (PLO) on daily rainfall was 126.2 mm, or 3 days-cumulative rainfall of 192.26 mm.